Prediction of Toxicities Induced by Sorafenib and Regorafenib (Precision Medicine Communications, 2022)
Currently, no biomarkers are available for detecting toxicities induced by the vascular endothelial growth factor (VEGF) tyrosine kinase inhibitors (TKI). Quintanilha and colleagues employed a discovery-validation approach to identify the markers of toxicities induced by these agents. A total of 140 cancer patients treated with Sorafenib (TARGET) were genotyped for 56 single nucleotide polymorphisms (SNPs). A separate cohort of 201 sorafenib-treated patients was tested for associations between grade ≥2 toxicities and the most significant SNPs. Specific SNPs displayed an association with composite toxicities, dermatological toxicities, diarrhea, and grade ≥2 hypertension. The association with grade ≥2 toxicities with the validated SNP was further investigated in 82 (Italian cohort) and 107 (LCCC 1029) patients administered regorafenib. Logistic regressions were employed to elucidate SNP-toxicity associations, followed by a meta-analysis of the conducted research for inverse variance. The results demonstrated that the presence of SNPs in KDR increased the risk of grade ≥2 composite toxicities in TARGET patients. In the Italian cohort, toxicities were associated with the variant rs4864950. Thus, their studies identified a predictor of VEGF TKI-induced toxicities. The Pharmacogenomics Journal (2022) DOI: 10.1038/s41397-022-00279-3.